Artificial Imagination and the History of Images - Català Domènech, Josep M. (Eikón / Imago, 2024)
Artificial intelligence, the last frontier of our deranged humanism, is the framework within which artificial image production systems appear. This is forcing us to reconsider the concepts of imagination and creativity while establishing a deep cut regarding the history of art in general and that of images in particular, a caesura or disruption that has much to do with the unbalanced state of the contemporary subject. The article intends to analyze the new type of artificial images and the panorama of visual culture in which they are generated, emphasizing the general phenomenology of the contemporary image and its relationship with thinking.